Validation of atmospheric evaporation duct in the eastern Indian Ocean - Qi, Zhe; Mao, Huabin; Qiu, Chunhua; Qi, Yongfeng (Frontiers in Earth Science, 2024)
An atmospheric duct is an anomalous atmospheric structural phenomenon that causes trap refraction in the troposphere to change the propagation paths and ranges of electromagnetic waves, thereby increasing the detection distances of radar and other communications. Atmospheric ducts include evaporation, surface, and elevated ducts. Evaporation ducts are commonly found near the sea surface and can impact electromagnetic wave propagation, radar communication, and livelihood applications at low altitudes. The meteorological environment of the Indian Ocean is complex, and the characteristics of its evaporation duct are still poorly understood. We validate four select atmospheric duct models using the observed evaporation duct height (EDH) in the Indian Ocean and present their spatial as well as temporal characterizations in spring using in situ meteorological variables. The results show that the EDH derived using the Babin model has the lowest bias with the observed value; thus, the Babin model can be used by researchers in the future to study changes to the EDHs in sea areas with similar seasonal conditions. The EDH in the Indian Ocean has diurnal variations, with higher (lower) values during the daytime (nighttime). The EDH has a negative correlation with the relative humidity, and the standard deviation of the EDH is largest when the relative humidity is 90%. The EDH has the maximum value when the wind speed is in the range of 8–14 m/s and when the air–sea temperature difference is zero, i.e., ∆T=Tair−Tsea=0. This study validates four different EDH models in the Indian Ocean, thus broadening our knowledge on the tropical atmospheric boundary layer.